Development of Electronic Comic Based on Realistic Mathematics Learning to Improve Students' Concept Comprehension Ability - Saragih, Patricia; Siregar, Budi Halomoan (Jurnal Pendidikan Matematika, 2025)
This research is motivated by the low student concept comprehension ability caused by the teacher-centered learning process and the absence of additional media used during the learning process. The purpose of this research is to develop an electronic comic based on Realistic Mathematics Learning with valid, practical, and effective criteria in improving the ability to understand concepts. This research uses the ADDIE development model: analysis, design, development, implementation and evaluation. The data collection techniques used are observation, interviews, questionnaires, and tests. Instruments for data collection include electronic comic validity questionnaire sheets, practicality questionnaires from teachers and students, concept comprehension ability tests, and student response questionnaires. The research findings show that electronic comics based on realistic mathematics learning developed on social arithmetic materials are suitable for use as a learning medium that can improve students' concept comprehension ability because they have been declared valid, practical, and effective. This is based on the results of the validation from media expert 4.5 (very valid) and 4.41 (very valid) from the material expert, the results of the practicality questionnaire from the teacher of 90% (very practical), and the results of the practicality questionnaire from students of 80.18% (very practical), the results of the test of students' conceptual comprehension ability, including (1) the completeness of classical concept comprehension of 87.18%; (2) the achievement of each indicator of concept comprehension of 97.20%, 97.20%, 74.35%, and 69.23%; (3) increased conceptual comprehension ability with N-Gain by 0.73; and (4) positive response from students of 90.25%.